2005
DOI: 10.1103/physrevb.71.035314
|View full text |Cite
|
Sign up to set email alerts
|

Chemically orderedAlxGa1xNalloys: Spontaneous formation of natural quantum wells

Abstract: We combine transmission electron microscopy, high-resolution x-ray diffraction, cathodoluminescence, and photoluminescence experiments with first-principles calculations to study the formation, thermodynamic stability, structural, and optical properties of chemically ordered Al x Ga 1−x N alloys ͑0 Ͻ x Ͻ 1͒. Our results reveal that group-III-nitride surfaces exhibit chemically highly sensitive adsorption sites at step edges and that these sites can be used to kinetically engineer chemically ordered Al x Ga 1−x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 20 publications
1
71
0
Order By: Relevance
“…In addition, Albrecht et al have measured a ;100 meV shift in the bandgap of a random alloy with respect to a disordered alloy of similar AlN mole fraction. 12 Ordering in AlGaN alloys was first reported by Korakakis et al, who observed the spontaneous formation of 2ML superlattices consisting of alternating AlN and GaN monolayers along the growth direction (0001) when the films were deposited under low III/V flux ratio conditions. 13 The existence of ordering was verified by the observation of the odd reflections (0001), (0003), etc.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, Albrecht et al have measured a ;100 meV shift in the bandgap of a random alloy with respect to a disordered alloy of similar AlN mole fraction. 12 Ordering in AlGaN alloys was first reported by Korakakis et al, who observed the spontaneous formation of 2ML superlattices consisting of alternating AlN and GaN monolayers along the growth direction (0001) when the films were deposited under low III/V flux ratio conditions. 13 The existence of ordering was verified by the observation of the odd reflections (0001), (0003), etc.…”
Section: Resultsmentioning
confidence: 94%
“…On the other hand, the similar periodic sequence of Ga-rich ultrathin clusters may occur as the formation of group-III bilayers owing to the different coordination of the group-III atoms at the step edges of the wurtzite AlGaN layers. The complex kinetics of such Gaincorporation has been studied both theoretically [18,19] and experimentally [9,20].…”
Section: Contributedmentioning
confidence: 99%
“…The spontaneous chemical ordering is similar to what was observed in AlGaN 16,17,18 and InGaN films 19 . Theoretically, the ordering in wurtzite Al x Ga 1-x N was suggested to be driven by the different binding energy of Al-N bond and Ga-N bond 20,21 . The adatom surface diffusion generally allows the incorporation of Al and Ga atoms at their different preferential sites, leading to the ordering sequence of Al-rich and Ga rich areas along the growth axis.…”
mentioning
confidence: 99%